2008
DOI: 10.1017/s1074070800002376
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Adoption of Cow-Calf Production Practices in Oklahoma

Abstract: Most technology adoption research has focused on crops. Primary data were used to determine differences in management practices among two groups of Oklahoma cow-calf producers based on herd size and cattle income dependence. Significant differences were noted between two groups of producers (smaller operations with less dependence on cattle versus larger with more dependence on cattle) in 79% of the management practices examined. Logit models determined factors influencing the probability of adopting 17 recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 9 publications
7
39
0
3
Order By: Relevance
“…According to De Souza et al (1993), farmers with at least a high school education have a 20 % increase in the likelihood of adoption. This finding is also in line with the past reports by Mussei et al (2001), Ward et al (2008) and .…”
Section: Adoption Of the Recommended Technologysupporting
confidence: 94%
“…According to De Souza et al (1993), farmers with at least a high school education have a 20 % increase in the likelihood of adoption. This finding is also in line with the past reports by Mussei et al (2001), Ward et al (2008) and .…”
Section: Adoption Of the Recommended Technologysupporting
confidence: 94%
“…There are many studies examining the use of technological components or factors that limit the application of innovations in livestock production systems (32)(33)(34) . In the present study, we identified that the use of technological innovations is low and very similar between producers (innovations related to food and use fodder less than 16 %, using concentrate was less than 11 %, milk management practices was between 22 and 11 %, innovations related to reproductive management was less than 6 %; Tables 4, 5).…”
Section: Infrastructure and Managementmentioning
confidence: 99%
“…Several studies about the adoption of new technologies and practices in agriculture revealed that producer's socio-economic attributes play an important role (e.g., Adesina and Chianu, 2002;Banerjee et al, 2008;Kim, Gillespie, and Paudel, 2005;Nagubadi et al, 1996;Nkamleu and Adesina, 2000;Paudel et al, 2008;Rahm and Huffman, 1984;Ward et al, 2008). The age of the primary producer is represented by the variable AGE.…”
Section: The Explanatory Variablesmentioning
confidence: 99%
“…9 As BMPs require good management and decisions making skills to obtain optimal results, it can be conjectured that education attainment of the primary producer is likely to significantly influence the decision to adopt a BMP Gillespie, Kim, and Paudel, 2007;Paudel et al, 2008;Ward et al, 2008). The average of this ordered variable centers between technical and college degrees.…”
Section: The Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation